An Evaluation of Readers Services at the University of Science and Technology Library- Kumasi, Ghana. Part III (Journal of Science and Technology, 2016)
The study sought to evaluate primarily reader services of the U.S.T Library. This was to assess its perfomance as regards the functions expected of a University Library that supports learning/ study, teaching and research, or to see how effectively the reader services unit of the Library has been rendering such services.